Korelasi Regulasi Diri Terhadap Berpikir Kritis Fisika Siswa SMAN 1 Sinunukan Kelas X Tahun Ajaran 2023-2024 - asepmahadan; Eni Sumanti Nasution; Kasmawati (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2024)
The aim of this research is based on the background, namely to determine the correlation between self-regulation and physics learning outcomes at SMAN 1 Sinunukan Class X for the 2023-2024 academic year. . The formulation of the problem in this research is whether there is a correlation between self-regulation and the physics learning outcomes of students at SMAN 1 Sinunukan Class X for the 2023-2024 academic year. The sample in this research was students of X SMAN 1 Sinunukan with a total of 30 students. The instrument in the research is a questionnaire to measure self-regulation and critical thinking with questions in the form of a description test. The type of research is correlation research. Data analysis techniques use normality tests, homogeneity. Hypothesis tests use regression tests. 1. The results of the analysis show that there is a relationship between self-regulation and critical thinking of 0.018. It can be seen that the significant contribution is smaller than 0.05 and the coefficient of the calculated r value is 53 with sufficient limits.